2016
DOI: 10.1108/ijaim-07-2015-0044
|View full text |Cite
|
Sign up to set email alerts
|

The association between abnormal audit fees and audit quality after IFRS adoption

Abstract: Purpose This paper aims to examine how the relationship between abnormal audit fees and audit quality changed after adoption of the International Financial Reporting Standards (IFRS) in Korea. Design/methodology/approach Using empirical data collected over the period from 2008 to 2013, this study analyzes the association between abnormally high/low audit fee and audit quality. This study uses linear regression to test the hypothetical relation using discretionary accrual as a proxy for audit quality. Findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 65 publications
2
32
1
4
Order By: Relevance
“…In previous attempts to resolve these contrasting arguments, countries have been compared [14,15,19,21,37], or studies have been limited to companies in one country [18,[20][21][22][23][38][39][40][41]. As a result, in the main results of these studies, it turned out that accounting quality was affected more by the reasons for companies' adoption of IFRS, the compulsory enforcement in the countries that adopted them, and their legal and institutional environments than by the act of IFRS adoption [8,[14][15][16][17][18]20,21,37,40].…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…In previous attempts to resolve these contrasting arguments, countries have been compared [14,15,19,21,37], or studies have been limited to companies in one country [18,[20][21][22][23][38][39][40][41]. As a result, in the main results of these studies, it turned out that accounting quality was affected more by the reasons for companies' adoption of IFRS, the compulsory enforcement in the countries that adopted them, and their legal and institutional environments than by the act of IFRS adoption [8,[14][15][16][17][18]20,21,37,40].…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…They reported ''the regulatory and legislative authorities became concerned that price-based competition could cause deterioration in audit quality'' and that ''public agencies and the popular press suspected that increasing competition for audit services could lead to underpricing'' (Behn et al 2009, 132-133). Their data were from 1999-2004, however, and more recent studies of Korean data have not reported the same issue (Kwon, Lim, and Simnett 2014;Jung, Kim, and Chung 2016).…”
Section: Levelmentioning
confidence: 73%
“…Moreover, the potential monopoly created by Big 4 companies does not seem to be affected by the additional expenses, which are expected to be charged by Big 4. Financial reporting according to the IFRS increases the number of companies audited by Big 4 , although the audit fees are higher for this type of auditors (Jung, 2015). Moreover, the audit market in Romania appears to be concentrated for the analysed period, and the power of non-Big 4 companies is not strong after 2012 (Table 1), after the adoption of IFRS became mandatory.…”
Section: Resultsmentioning
confidence: 98%